(untitled) (The Agriculturists, 2016)
Seven individuals of introgressed Brassica lines (Binasarisha-5/Daulot) and two of their parental lines were used for this study to estimate genetic variability using three randomly amplified polymorphic DNA (RAPD) markers (61AB10G1, 72AB10G12 and 73AB10T13). A total of 23 clear bands were scored, of which 21 (91.30%) bands were proved to be polymorphic. The highest proportion of polymorphic loci and gene diversity values were 43.48% and 0.187, respectively in the line five of Binasarisha-5/Daulot. The lower proportion of polymorphic loci and gene diversity values were 8.70% and 0.034; 8.70% and 0.026 in the line seven of the cross and one parent, Daulot, respectively. The co-efficient of gene differentiation (Gst) and gene flow (Nm) values were 0.677 and 0.237, found respectively from the Popgene analysis. Result of cluster analysis indicated that the nine accessions were capable of being classified into two major groups - one consists of only one parent Daulot (Brassica juncea) while another consists of Binasarisha-5 (Brassica napus) and all introgressed lines of C6 generation (treated with colchicine in C1 generation) resulted from the cross B. napus and B. juncea. Introgressed line seven and Binasarisha-5 showed the lowest genetic distance of 0.077. Higher similarity was found between Binasarisha-5 and introgressed progenies. Introgressed line one and Daulot showed the highest genetic distance of 0.709, which can be used as germplasm for breeding program that aim to improve Brassica. It was concluded that RAPD markers can be used for the study of molecular characterization and diversity in Brassica. The Agriculturists 2016; 14(1) 122-133